PENGARUH ORIENTASI KEWIRAUSAHAAN DAN ORIENTASI PASAR TERHADAP KINERJA PERUSAHAAN MELALUI KEUNGGULAN BERSAING DAN PERSEPSI KETIDAKPASTIAN LINGKUNGAN SEBAGAI PREDIKSI VARIABEL MODERASI (Survey pada UMKM Perdagangan di Kabupaten Kebumen) - Setyawati, Harini Abrilia (P4M STIE Putra Bangsa, 2013)
This research is done on the UMKM retail in Kebumen Regency, by the title Ã¢â‚¬Å“The influence of entrepreneurship and market orientation to performance by competitive advantage as mediation and it is moderated by the perception of environment uncertaintyÃ¢â‚¬Â The purpose of this research is testing the influence of entrepreneurship and market orientation to performance by competitive advantage as mediating and the perception of environment uncertainty as moderating variable. This research is quantitative approach using survey method. The number of respondents is 100 shop owners in Kebumen regency which is determined by using SlovinÃ¢â‚¬â„¢s formula. AnalysisÃ¢â‚¬â„¢s device that used is Ã¢â‚¬Å“Partial Least SquareÃ¢â‚¬Â From the result of this research and data analysis can be concluded that entrepreneurship orientation gives positive impact to market orientation, entrepreneurship orientation gives positive impact to competitive advantage, market orientation does not influence to competitive advantage, entrepreneurship orientation does not influence to performance, market orientation does not influence to performance, competitive advantage does not influence to performance, entrepreneurship and market orientation does not affects to relation performance and competitive advantage and perception of environment uncertainty which does not moderating the relation of competitive advantage and performance.